2013
DOI: 10.1111/evj.12157
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and long‐term follow‐up of distichiasis, with special reference to the Friesian horse: A case series

Abstract: There is a breed predisposition of distichiasis in the Friesian horse. In Friesian horses that present with uni- or bilateral corneal irritation or corneal ulceration, careful examination of the eyelid margins should be performed to diagnose distichiasis. Electrocautery is a valid and successful therapeutic modality which is minimally invasive, inexpensive, has a low complication rate and is easy to perform in the standing sedated horse. The recurrence rate is low in horses with less than 5 distichiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…1 4 8 Reinstein et al 9 report depigmentation resolves with time following transconjunctival electrocautery to remove distichiasis. 8 Follow-up of cases in part 2 of this study revealed that depigmentation remained in five dogs; however, this was thought to be cosmetic and not causing any clinical signs of ocular discomfort. Another reported disadvantage of electroepilation is focal destruction of the meibomian gland.…”
Section: Discussionmentioning
confidence: 69%
“…1 4 8 Reinstein et al 9 report depigmentation resolves with time following transconjunctival electrocautery to remove distichiasis. 8 Follow-up of cases in part 2 of this study revealed that depigmentation remained in five dogs; however, this was thought to be cosmetic and not causing any clinical signs of ocular discomfort. Another reported disadvantage of electroepilation is focal destruction of the meibomian gland.…”
Section: Discussionmentioning
confidence: 69%
“…Utter and Wotman [11] describe distichiasis causing recurrent corneal ulceration in two Friesian horses located in the United States. In a retrospective analysis, Hermans and Ensink [12] reported a high rate of recurrence despite treatment, particularly when individuals had five or more aberrant lashes, and that all cases presented with irritation or ulceration [12]. The number of Friesian cases presented in these two reports suggests a genetic basis for distichiasis in this breed.…”
Section: Introductionmentioning
confidence: 92%
“…Meibomian glands affected with distichiae are structurally abnormal based on meibography [6]. While distichiae can be shorter, thinner and less pigmented than normal eyelashes [8], they can also be thick and stiff and thus capable of causing tearing, corneal irritation, keratitis, and corneal erosions or ulcers, which can impact ocular comfort and vision, and may lead to secondary infection [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Distichiasis is uncommonly observed in horses, cats, and ferrets. [ 15 16 ] In contrast to the distichiasis seen in humans, which can be acquired, distichiasis in animals is usually congenital. Its inheritance is presumed to be autosomal dominant; however, it has not been formally proven.…”
Section: Distichiasis In Animal Populationmentioning
confidence: 99%